2023
DOI: 10.33736/bjrst.5109.2023
|View full text |Cite
|
Sign up to set email alerts
|

Species Diversity and Assemblage of Mangroves at Setiu Wetland, Terengganu, Malaysia

Abstract: Mangroves in wetland ecosystems are diverse and play significant role in the adjacent communities on which they are dependent for their livelihoods. It is also important for fishery resources and nutrient inputs in marine and brackish water ecosystems. However, little is known about the tropical wetland lagoon ecosystems, particularly mangrove diversity and assemblages. Therefore, this present study was initiated to observe the mangrove species diversity and assemblages together with the conservation status in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In addition, the neighbourhood actively promotes the protection of wetlands. A separate study by Rahman et al (2023) examined Setiu Wetland mangrove species diversity and assemblage. The wetland research found 20 mangrove species, 11 genera, and nine families.…”
Section: Literature Review Sustainable Wetland Challenges In Malaysiamentioning
confidence: 99%
“…In addition, the neighbourhood actively promotes the protection of wetlands. A separate study by Rahman et al (2023) examined Setiu Wetland mangrove species diversity and assemblage. The wetland research found 20 mangrove species, 11 genera, and nine families.…”
Section: Literature Review Sustainable Wetland Challenges In Malaysiamentioning
confidence: 99%